Teaching–learning-based optimization algorithm for multi-area economic dispatch - Basu, M. (Energy (Oxford), 2014)
This paper presents teaching–learning-based optimization algorithm for solving MAED (multi-area economic dispatch) problem with tie line constraints considering transmission losses, multiple fuels, valve-point loading and prohibited operating zones. TLBO (teaching–learning-based optimization) is one of the recently proposed population based algorithms which simulates the teaching–learning process of the class room. It is a very simple and robust global optimization technique. The effectiveness of the proposed algorithm has been verified on three different test systems, both small and large, involving varying degree of complexity. Compared with differential evolution, evolutionary programming and real coded genetic algorithm, considering the quality of the solution obtained, the proposed algorithm seems to be a promising alternative approach for solving the MAED problems in practical power system. •This paper presents teaching–learning-based optimization algorithm for solving multi-area economic dispatch problem.•Teaching–learning-based optimization (TLBO) is one of the recently proposed population based algorithm.•It simulates the teaching–learning process of the class room. It is a very simple and robust global optimization technique.•The effectiveness of the proposed algorithm has been verified on three different test systems, both small and large.